Introducing BF++: A C++ Framework for Cognitive Bio-Feedback Systems Design - Bianchi, L.; Babiloni, F.; Cincotti, F.; Salinari, S.; Marcian, M.G. (Methods of Information in Medicine, 2003)
Objective: This paper addressed the issue of building-up a framework for the realization of several cognitive bio-feedback (CBF) systems. It minimizes the programming effort and maximizes the efficiency and the cross-platform portability so that it can be used with many platforms (either software or hardware).Methods: A generic CBF system was decomposed into six modules: acquisition, kernel, feedback rule, patient feedback, operator user interface and persistent storage. The way in which these modules interact was defined by immutable software interfaces in a way that allows to completely substitute a module without the need to modify the others.Results: Three Brain Computer Interface engines were developed with less than 40 lines of C++ code each. They can also be used under virtually any platform that supports an ANSI C++ compiler.Conclusion: A framework for the implementation of a wide range of CBF systems was developed. Compared to the other approaches that are described in the literature, the proposed one is the most efficient, the most portable across different platforms, the most generic and the one that allows the realization of the cheapest final systems.
Keywords: Augmentative communication; cognitive bio-feedback; bio-feedback system design